Utilising Arabic-origin loanwords in teaching Malay as a foreign language - Uni, K. (Universiti Putra Malaysia, 2015)
After Sanskrit, Arabic is the second-largest donor language to the Malay vocabulary. Through a vocabulary survey containing 40 Arabic-origin Malay loanwords, this study examines the utility of explicit presentation of Arabic-origin Malay loanwords and their etymologies in teaching Malay as a foreign language to Arabic speakers. The participants included 20 Arabic-speaking students at the University of Malaya, Kuala Lumpur, Malaysia. The participants averaged 24.4 correct answers and 17.6 newly learned vocabulary items. At 5% significance level, a clear significant difference was found in participants' scores before and after the presentation of the loanwords' Arabic etymologies (p = .000). This study concluded that the explicit presentation of Arabic-origin Malay loanwords containing one or more modified consonants or vowels and their etymologies benefits Arabic speakers who are learning Malay as a foreign language.